Efficacy of Intra Alveolar Placement of Chlorhexidine 0.2% with Metronidazole 10mg Gel for Prevention of Dry Socket - Ameet Kumar, Safia, Manoj Kumar, Iffat Panhwar, Syed Ghazanfar Hassan, Salman Shams, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the efficacy of intra alveolar placement of chlorhexidine 0.2% with metronidazole 10mg gel for prevention of dry socket. Material and Methods: This comparative study included patients having only mandibular mesioangular Class 1, Class A impaction with same difficulty index. Patients were divided into two groups. In group A After the extraction of tooth Chlorhexidine 0.2% with Metronidazole 10mg was applied in the socket, while in group B After the extraction of tooth socket was irrigated with normal saline and patients were recalled for assessment of pain by wong bakers scale (facies) on day 1, day 3 and day 5 post-operatively. Results: The average age of patients of group A was 28.38+4.52 years and average age of group B patients was 37.04+7.32 years. Females were found in majority in both groups as 63.6% in group A and 52.3% in group B. Average of pain score (WBFPS) on first to 5th operative days was significantly lower in group A as compared to group B, p-values were quite significant. Mean duration of surgery was almost equal among both groups. Frequency of dry socket was significantly lower in group A as 47.7% in contrast to group B as 88.6%, (p-0.001). Results: Intra alveolar placement of chlorhexidine 0.2% with metronidazole 10mg gel was found to be effective in terms of lower post-operative pain and prevention of dry socket in contrast to normal saline